2022
DOI: 10.1186/s13643-022-01884-w
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, risk factors and outcomes of anaemia in South African pregnant women: a systematic review and meta-analysis

Abstract: BackgroundAnaemia is associated with maternal and perinatal morbidity and mortality. The pooled prevalence of anaemia in the South African (SA) pregnant population was ascertained by systematically reviewing available literature. Severity, risk factors (HIV, tuberculosis, race, province, year of study), maternal morbidity and mortality (hypertensive disorders of pregnancy), birth outcomes (including low birth weight) and supplementation during pregnancy were also described.MethodsEligible studies reported on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 68 publications
(108 reference statements)
5
22
1
2
Order By: Relevance
“…The prevalence here is estimated to be between 46.3 and 60%. 14 From our study and few other studies reported so far in Malaysia highlights that there has not been a change in prevalence over the last two decades. 15 As for ethnicity, our study found that the Indians had a highest prevalence followed by Chinese and Malays.…”
Section: Discussionsupporting
confidence: 61%
“…The prevalence here is estimated to be between 46.3 and 60%. 14 From our study and few other studies reported so far in Malaysia highlights that there has not been a change in prevalence over the last two decades. 15 As for ethnicity, our study found that the Indians had a highest prevalence followed by Chinese and Malays.…”
Section: Discussionsupporting
confidence: 61%
“…6 And although, a recent review paper. 9 attributed low birth weight and hypertensive disease of pregnancy to anaemia, a multicentre and multiethnic study 6 showed no significant relationship between anemia in pregnancy and adverse birth outcome.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,8 In this regard, even pregnant women taking routine haematenic supplements have been found to have the anemic trend due to varied and disproportionate requirements and hormonal changes. 9,10 Indeed, iron supplementation as traditionally practiced during antenatal services, essentially corrects iron deficiency form of anaemia and may be appropriate only for the malnourished category of pregnant mothers. 9 Therefore, there are far many causes of anemia in pregnancy that iron supplements alone cannot address.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations